EFFECTS OF MACRO ELEMENTS AND MEDIUM REPLENISHMENT ON CELL SUSPENSION CULTURE OF PANAX GINSENG HA ET GRUSHV. IN VITRO - Nguyễn Văn Kết; Trương Thị Lan Anh (Tạp chí Khoa học Đại học Đà Lạt)
It has been demonstrated that the difference of macro-elements concentrations effect various on callus culture in vitro of Panax vietnamensis. The callus growths were the greatest in the medium supplemented with from 0.5 to 1.0- strength KNO3 and CaCl2, and 1.0-strength NH4H2PO4 and MgSO4. Moreover, the strategy of medium replenishment was helpful for cell suspension growth. And the maximum cell suspension growth was achieved with feeding of the 1/4MS at the end of 3rd.